2022
DOI: 10.3389/fpsyt.2021.791555
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Related Factors: A Comparison of Fathers and Mothers of Patients With Cleft Lip and/or Palate in China

Abstract: Background: Resilience has become a hot spot in the field of positive psychology to study life-change events. However, there were little information on resilience among the fathers and mothers of patients with cleft lip and/or palate respectively. The present study aimed to explore and compare the level and potential influential factors associated with resilience among fathers/mothers of patients with cleft lip and/or palate in China.Method: A cross-sectional study was carried out between April 2019 and July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Accumulating evidence confirms that hope is significantly protective for various mental disorders [ 21 , 22 ]. In addition, hope is also protective for individuals’ resilience [ 23 , 24 ]. Stress refers to the experience of distress when confronted with unpleasant threats or stressors and presents as perceived helplessness and a decrease in self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence confirms that hope is significantly protective for various mental disorders [ 21 , 22 ]. In addition, hope is also protective for individuals’ resilience [ 23 , 24 ]. Stress refers to the experience of distress when confronted with unpleasant threats or stressors and presents as perceived helplessness and a decrease in self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…However, these associations have not reached statistical significance in our study. Other studies in different contexts have reported mixed results, highlighting the need for further research to draw conclusive assertions regarding the relationship between gender and resilience (Abiola & Udofia, 2011; Losoi et al, 2013; Yuan et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…According to the results of hierarchical linear regression analysis, hope may have the strongest effect on stigma among renal dialysis patients, similar to previous studies on patients with other diseases ( 37 , 61 ). It has been reported that hope is related to almost all health outcomes ( 62 ) for two reasons. Rather, hope is a vital positive psychological variable.…”
Section: Discussionmentioning
confidence: 99%